Piezo1-pannexin-1-P2X3 axis in odontoblasts and neurons mediates sensory transduction in dentinal sensitivity - Ohyama, Sadao; Ouchi, Takehito; Kimura, Maki; Kurashima, Ryuya; Yasumatsu, Keiko; Nishida, Daisuke; Hitomi, Suzuro; Ubaidus, Sobhan; Kuroda, Hidetaka; Ito, Shinichirou; Takano, Masayuki; Ono, Kentaro; et al. (Frontiers in Physiology, 2022)
According to the “hydrodynamic theory,” dentinal pain or sensitivity is caused by dentinal fluid movement following the application of various stimuli to the dentin surface. Recent convergent evidence in Vitro has shown that plasma membrane deformation, mimicking dentinal fluid movement, activates mechanosensitive transient receptor potential (TRP)/Piezo channels in odontoblasts, with the Ca2+ signal eliciting the release of ATP from pannexin-1 (PANX-1). The released ATP activates the P2X3 receptor, which generates and propagates action potentials in the intradental Aδ afferent neurons. Thus, odontoblasts act as sensory receptor cells, and odontoblast-neuron signal communication established by the TRP/Piezo channel-PANX-1-P2X3 receptor complex may describe the mechanism of the sensory transduction sequence for dentinal sensitivity. To determine whether odontoblast-neuron communication and odontoblasts acting as sensory receptors are essential for generating dentinal pain, we evaluated nociceptive scores by analyzing behaviors evoked by dentinal sensitivity in conscious Wistar rats and Cre-mediated transgenic mouse models. In the dentin-exposed group, treatment with a bonding agent on the dentin surface, as well as systemic administration of A-317491 (P2X3 receptor antagonist), mefloquine and 10PANX (non-selective and selective PANX-1 antagonists), GsMTx-4 (selective Piezo1 channel antagonist), and HC-030031 (selective TRPA1 channel antagonist), but not HC-070 (selective TRPC5 channel antagonist), significantly reduced nociceptive scores following cold water (0.1 mL) stimulation of the exposed dentin surface of the incisors compared to the scores of rats without local or systemic treatment. When we applied cold water stimulation to the exposed dentin surface of the lower first molar, nociceptive scores in the rats with systemic administration of A-317491, 10PANX, and GsMTx-4 were significantly reduced compared to those in the rats without systemic treatment. Dentin-exposed mice, with somatic odontoblast-specific depletion, also showed significant reduction in the nociceptive scores compared to those of Cre-mediated transgenic mice, which did not show any type of cell deletion, including odontoblasts. In the odontoblast-eliminated mice, P2X3 receptor-positive A-neurons were morphologically intact. These results indicate that neurotransmission between odontoblasts and neurons mediated by the Piezo1/TRPA1–pannexin-1–P2X3 receptor axis is necessary for the development of dentinal pain. In addition, odontoblasts are necessary for sensory transduction to generate dentinal sensitivity as mechanosensory receptor cells.